Вибір чавуну для вставок у фрикційний елемент гальмівних колодок рухомого залізничного транспорту - Сіренко , Катерина Адольфівна; Мазур , Валерій Леонідович (Physico-technological Institute of Metals and Alloys, 2024)
The article reviews publications on the evaluation of the effectiveness of materials used for the manufacture of brake pads for railway rolling stock. The chemical composition, mechanical properties and performance characteristics of cast iron and composite brake pads made of rubber compound, including those equipped with cast iron inserts, are compared. It is shown that the chemical composition and mechanical properties of cast iron brake pads meet the requirements regulated in standards, in particular, in GOST 30249-97, which is currently in force in Ukraine. Composite brake pads are manufactured according to specifications that do not regulate the percentage of composite rubber compound components and their chemical composition, which is a violation of GOST 2.114-95. This excludes the possibility of controlling these main indicators of the pads' quality by their consumers. It has been confirmed that the main disadvantage of composite brake pads is the significantly low thermal conductivity of the composite rubber compound compared to the thermal conductivity of cast iron. Due to the low thermal conductivity of the friction element of brake pads made of this composite material and, as a result, insufficient heat dissipation from the friction zone between the pad and the wheel during train braking, the temperature in this zone can reach 900 °C. This is despite the fact that the self-ignition temperature of the composite rubber compound is (300...550) °C according to the technical specifications for composite pads. An increase in temperature changes the friction conditions of the pads on the rolling surface of the wheels and impairs the wear resistance of the pads. To mitigate the negative impact of the low thermal conductivity of the composite rubber compound, the friction element of composite brake pads is equipped with inserts made of cast iron, which has a relatively high thermal conductivity. Such a solution has a positive effect on the temperature regime of the pads and wheels, but does not provide a radical improvement in heat removal from the contact zone of brake pads with the wheels of moving vehicles. The mechanism of influence of the temperature in the contact zone of the pad with the wheel on the occurrence of defects in the rolling surface of wheels is considered. The toxicity of brake composite pads made of uncontrolled rubber compounds and the harmfulness of their wear products to human health and the environment are noted. Recommendations for the selection of cast iron for inserts in the friction material of brake pads are given. The article shows the prospects of using inserts made of partially graphitised cast iron.